Multimodality of @Tirto.id Instagram Content in Critical Discourse Analysis Teaching Materials - Sukirno; Suta Wardianto, Bayu (International Proceedings of Nusantara Raya, 2023)
Multimodality is a detailed effort in unveiling a visual that can be interpreted in the form of text. In critical discourse analysis originating from visualization in the form of images, multimodality helps reveal the visual modes contained in the visual image, with the study of multimodality in critical discourse analysis, symbolic meanings in the form of visual modes can be deciphered. The research seeks to describe the need for discourse analysis by using multimodality studies with research data sources in the form of @Tirto.id Instagram content. Furthermore, this study also explained the concept of learning critical discourse analysis by utilizing modality elements in @Tirto.id Instagram content. The research uses qualitative descriptive techniques by applying analytical descriptions to research data. In addition, this study uses reflective conceptual techniques to elaborate on the learning concept of critical discourse analysis by utilizing modality elements in @Tirto.id Instagram content. The results and discussion in the study describe CDA briefly along with the learning concept of Critical Discourse Analysis in Higher Education by utilizing the multimodality content of Instagram @Tirto.id content. Analysis and learning concepts that will be put forward starting from the introduction (containing learning outcomes—an explanation of Critical Discourse Analysis), material (in the form of how to analyze @Tirto.id Instagram content with Van Dijk theory), and closing (delivering suggestions in learning).